2009
DOI: 10.1007/s00439-009-0773-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of osteoporosis: accelerating pace in gene identification and validation

Abstract: Osteoporosis is characterized by low bone mineral density and structural deterioration of bone tissue, leading to an increased risk of fractures. It is the most common metabolic bone disorder worldwide, affecting one in three women and one in eight men over the age of 50. In the past 15 years, a large number of genes have been reported as being associated with osteoporosis. However, only in the past 4 years we have witnessed an accelerated pace in identifying and validating osteoporosis susceptibility loci. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 380 publications
(441 reference statements)
0
65
0
6
Order By: Relevance
“…Finally, there are several examples, including the LRP5 and SOST gene, where the role of certain proteins in bone homeostasis was initially identified by the study of monogenic bone disorders (4,6,13,14), which was subsequently confirmed by genetic association studies illustrating that natural variants within these genes had an influence on BMD in the general population (54). Interestingly, a recent genome-wide association study of BMD in individuals of European descent has showed that non-synonymous SNPs in the LRP4 gene are asso-ciated, providing further support for a role of LRP4 in bone metabolism (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are several examples, including the LRP5 and SOST gene, where the role of certain proteins in bone homeostasis was initially identified by the study of monogenic bone disorders (4,6,13,14), which was subsequently confirmed by genetic association studies illustrating that natural variants within these genes had an influence on BMD in the general population (54). Interestingly, a recent genome-wide association study of BMD in individuals of European descent has showed that non-synonymous SNPs in the LRP4 gene are asso-ciated, providing further support for a role of LRP4 in bone metabolism (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Such bone diseases and conditions include osteoporosis, osteoarthritis, heterotopic ossification (HO), Paget's disease, osteonecrosis of the femoral head (ONFH), and others. Extensive research on genetic variations and osteoporosis, has verified, to date, at least 15 genes including vita-min D receptor (VDR), lipoprotein receptor-related protein 5 (LRP5), sclerostin (SOST), osteoprotegerin (OPG), RANK/RANKL, and collagen type I alpha1 (COLIA1), as osteoporosis susceptibility genes, whereas, another >30 genes are promising candidate genes (23). Large genetic studies have also identified genetic variants within genes in signalling pathways involved in cartilage and bone biology, like the BMP pathway (e.g.…”
Section: Genetic Profile and Other Orthopaedic Conditions And Bone DImentioning
confidence: 99%
“…However, regulatory involvement of RUNX2 in LRP5 transcription has not been reported to date. Several allelic variants in the LRP5 gene have been associated with osteoporotic phenotypes such as bone mineral density (BMD) and fracture in different association-analysis approaches, such as single missense single-nucleotide polymorphism (SNP) analysis, gene-wide analysis, and even genome-wide analysis (GWA; reviewed by Li and colleagues (28) ). Therefore LRP5 is a confirmed osteoporosis susceptibility gene.…”
Section: Introductionmentioning
confidence: 99%